Potential decline in carbon carrying capacity under projected climate-wildfire interactions in the Sierra Nevada - Liang, Shuang; Hurteau, Matthew D.; Westerling, Anthony LeRoy (Scientific reports, 2017)
Ecosystem carbon carrying capacity (CCC) is determined by prevailing climate and natural disturbance regimes, conditions that are projected to change significantly. The interaction of changing climate and its effects on disturbance regimes is expected to affect forest regeneration and growth, which may diminish forest carbon (C) stocks and uptake. We modeled landscape C dynamics over 590 years along the latitudinal gradient of the U.S. Sierra Nevada Mountains under climate and area burned by large wildfires projected by late 21 st century. We assumed climate and wildfire stabilize at late-21 st century conditions (2090–2100) to facilitate analysis of lags between warming and changing CCC. We show that compared with historical (1980–2010) climate and wildfire conditions, projected scenarios would drive a significant decrease of up to 73% in mean total ecosystem carbon (TEC) by the end of the 590-year simulation. Tree regeneration failure due to intensified growing season dryness and increased area burned would substantially decrease forested area, transitioning the system from C sink to source. Our results demonstrate the potential for a lower CCC in the system due to extensive vegetation type conversion from forest to non-forest types, and suggest a decline in the contribution of Sierra Nevada forests to U.S. C sink.